Design of a thermal stress microfluidic platform to screen stability of therapeutic proteins in pharmaceutical formulations - O. Bortone; S. Fiorenza; M. Baldassarre; N. Falco; M. Amidi; T. Markkula; P.A. Netti; E. Torino (Current Research in Biotechnology)
Therapeutic proteins have great potentialities for the care of a wide spectrum of diseases, for which other small synthetic drugs result ineffective. Due to challenges related to their immunogenicity, the journey of biologics into clinics still faces obstacles. Among the causes of protein immunogenicity, their natural propensity to aggregation is crucial, indeed, to study their stability, pharmaceutical formulations are generally exposed to diverse environmental physicochemical conditions. Traditional approaches to explore protein behavior are effort-demanding, lengthy and expensive, resulting in a limited knowledge of biomolecule stability. There is an urgent need to develop faster and more cost-effective technologies for biological formulation development. In this work, the conceptualization, design and implementation of a modular and automated microfluidic platform to provide thermal stress to highly concentrated and viscous pharmaceutical formulations is presented. The microfluidic platform validity in terms of reliability and comparability to a forced degradation batch-wise stimulation is demonstrated by thermally stimulating and analyzing through SE-HPLC (Size Exclusion – High Performance Liquid Chromatography) different high concentration (> 100 mg/ml) therapeutic nanobody-based formulations. Remarkably, the ranking of the formulations returned by the microfluidic thermal stress platform follows the same trend obtained through well-established industrial in-batch stimulations. Furthermore, data coming from microfluidic stimulations well correlates to outcomes coming from industrial methodologies for storage and accelerated stability studies.